Assays of plasma dehydrocholesteryl esters and oxysterols from Smith-Lemli-Opitz syndrome patients - Liu, Wei; Xu, Libin; Lamberson, Connor R.; Merkens, Louise S.; Steiner, Robert D.; Elias, Ellen R.; Haas, Dorothea; Porter, Ned A. (Journal of lipid research, 2013)
Smith-Lemli-Opitz syndrome (SLOS) is caused by mutations in the gene encoding 3β-hydroxysterol-Δ7-reductase and as a result of this defect, 7-dehydrocholesterol (7-DHC) and 8-dehydrocholesterol (8-DHC) accumulate in the fluids and tissues of patients with this syndrome. Both 7- and 8-DHC are susceptible to peroxidation reactions, and several biologically active DHC oxysterols are found in cell and animal models of SLOS. Ex vivo oxidation of DHCs can be a confounding factor in the analysis of these sterols and their esters, and we developed HPLC/MS methods that permit the direct analysis of cholesterol, 7-DHC, 8-DHC, and their esters in human plasma, thus avoiding ex vivo oxidation. In addition, three oxysterols were classified as endogenously formed products by the use of an isotopically-labeled 7-DHC (d7-7-DHC) added to the sample before workup, followed by MS analysis of products formed. Analysis of 17 SLOS plasma samples shows that 8-DHC linoleate correlates better with the SLOS severity score of the patients than other sterols or metabolites, including cholesterol and 7-DHC. Levels of 7-ketocholesterol also correlate with the SLOS severity score. 8-DHC esters should have utility as surrogate markers of severity in SLOS for prognostication and as endpoints in clinical trials.
Available online 4 January 2021
Published, JLR Papers in Press, October 16, 2012
Gesehen am 19.05.2021